Functional flexibility in a spider's Orb Web - Mulder, T; Mortimer, B; Vollrath, F (Company of Biologists, 2020)
Web spiders rely on vibrations propagated via their web to identify, locate and capture entangled prey. Here we experimentally test the robustness of the orb weaver's predation strategy when webs are severely distorted and silk tensions are drastically altered throughout the web, a common occurrence in the wild. We assessed prey identification efficiency by comparing the spider's initial reaction times towards a fruit fly trapped in the web, we measured location efficiency by comparing times and the numbers of tugging bouts performed, and we determined capture efficiency by comparing capture times. It emerged that spiders are capable of identifying, locating and capturing prey in distorted webs albeit taking somewhat longer to do so.